55.7k views
3 votes
If p is the hypothesis of a conditional statement and q is the conclusion, which is represented by ~p → ~q?a-the original conditional statementb-the inverse of the original conditional statementc-the converse of the original conditional statementd-the contrapositive of the original conditional statement

2 Answers

5 votes

Given a conditional statement
P \implies Q, you have:

  • The original statement is
    P \implies Q
  • The inverse statement is the negation of both sides:
    \lnot P \implies \lnot Q
  • The converse statement switches hypothesis and conclusion:
    Q \implies P
  • The contrapositive statement is switching hypothesis and conclusion, and negating both:
    \lnot Q \implies \lnot P

So, in your case, you have the inverse statement.

User Moktor
by
5.0k points
0 votes

NOT P → NOT Q is the INVERSE

Answer: B

User Zavanton
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.